Molecular imaging of cardiovascular inflammation. (14th October 2021) - MacRitchie, Neil; Noonan, Jonathan; Guzik, Tomasz J.; Maffia, Pasquale
Abstract : Cardiovascular diseases (CVDs), including atherosclerosis, are chronic inflammatory diseases characterised by a complex and evolving tissue micro‐environment. Molecular heterogeneity of inflammatory responses translates into clinical outcomes. However, current medical imaging modalities are unable to reveal the cellular and molecular events at a level of detail that would allow more accurate and timely diagnosis and treatment. This is an inherent limitation of the current imaging tools, which are restricted to anatomical or functional data. Molecular imaging—the visualisation and quantification of molecules in the body—is already established in the clinic in the form of PET, yet the use of PET in CVD is limited. In this visual review, we will guide you through the current state of molecular imaging research, assessing the respective strengths and weaknesses of molecular imaging modalities, including those already being used in the clinic such as PET and MRI and emerging technologies at preclinical stage, such as photoacoustic imaging. We discuss the basic principles of each technology and provide key examples of their application in imaging inflammation in CVD and the added value into the diagnostic decision‐making process. Finally, we discuss the barriers to the rapid successful clinical translation of these novel diagnostic modalities. LINKED ARTICLES: This article is part of a themed issue on Molecular imaging ‐ visual themed issue. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.21/issuetoc